Escherichia coli heme oxygenase modulates host innate immune responses - Maharshak, Nitsan (Microbiol Immunol, 2015)
Induction of mammalian heme oxygenase-1 and exposure of animals to carbon monoxide ameliorates experimental colitis. When enteric bacteria, including Escherichia coli, are exposed to low iron conditions, they express an heme oxygenase-like enzyme, chuS, and metabolize heme into iron, biliverdin and carbon monoxide. Given the abundance of enteric bacteria residing in the intestinal lumen, we hypothesized that commensal intestinal bacteria may be a significant source of carbon monoxide, with the consequence that enteric bacteria expressing chuS and other heme oxygenase -like molecules suppress inflammatory immune responses through release of carbon monoxide. Carbon monoxide exposed mice have altered enteric bacterial composition and increased E. coli 16S and chuS DNA by real-time PCR. Moreover, severity of experimental colitis correlates with increased E. coli chuS expression in IL-10 deficient mice. To explore functional roles, E. coli were genetically modified to overexpress chuS or the chuS gene was deleted. Co-culture of chuS-overexpressing E. coli with bone marrow derived macrophages results in decreased IL-12 p40 and increased IL-10 secretion compared to wild-type or chuS-deficient E. coli. Mice infected with chuS-overexpressing E. coli have increased levels of hepatic carbon monoxide and decreased serum IL-12 p40 compared to mice infected with chuS-deficient E. coli. Thus, carbon monoxide alters the composition of the commensal intestinal microbiota and expands E. coli populations harboring the chuS gene. These bacteria are capable of attenuating innate immune responses through expression of chuS. Bacterial heme oxygenase -like molecules and bacterial-derived carbon monoxide may represent novel targets for therapeutic intervention in inflammatory conditions.